Evaluation of English Texts' Readability in National Examination in Indonesia - Mohamad Syafri (Ahmad Dahlan Journal of English Studies, 2022)
The National Examination is still considered one of the main national-scale tests. As one of the subjects tested, English has used many texts in National Examination. This study evaluates the quality of reading texts' readability in the English National Examination for Junior High School from 2014/2015-2018/2019. 2019/2020 and 2020/2021 are not tested due to their cancellation under the health protocol implemented by the government. The study follows the quantitative descriptive evaluation approach. The SMOG formula is used to measure the texts' readability. From the last five English National Examination tests, 31 texts were tested. There are three aspects evaluated: the number of texts per test, words per text, and readability. The study results showed that there are 87 texts used in total from 2014-2015 to 2018/2019. Among them, only 31 texts exceed 150 words. The average texts quantity is 6,2, and the annual growth is 13,6%. The average number of words per text is 224,1, and the yearly growth is 4,6%. The main aspect, the average score of texts readability is 9,71 or at the level "Easy to Read" suitable to 6th Grader, and the annual growth of texts' readability is 3,9%. The study results show an improvement in quantity and quality, specifically for the readability, of the texts used in the English National Examination.